Balancing academic freedom and research integrity through virtue ethics in the use of AI in open distance education - Prinsloo, C.; Ramashego, S. M.; Visagie, R. G.; Tjano, N. (South African Journal of Higher Education, 2025)
In a rapidly evolving educational landscape shaped by Society 5.0, the integration of Artificial Intelligence (AI) into Open Distance Education (ODE) presents both transformative opportunities and ethical challenges. While AI enhances access, personalises learning, and streamlines administration, its usage raises concerns about academic freedom, research integrity, and ethical conduct. This article explores the balancing act required to leverage AI’s capabilities without compromising the values of academic freedom and integrity. A virtue ethics framework is proposed to facilitate ethical AI deployment, prioritising virtues like integrity, accountability, and justice. Through a narrative literature review, the article examines the intersection of AI, academic freedom, and research integrity, proposing a conceptual model rooted in virtue ethics. The framework promotes a responsible AI-driven educational model that respects intellectual autonomy, mitigates ethical risks, and enhances research credibility in ODE. The article concludes with recommendations for implementing virtue ethics in AI governance within academic institutions, emphasising a sustainable approach to maintaining ethical standards in an AI-enhanced educational environment.